PROSPECTS FOR THE DEVELOPMENT OF ONLINE TRAVEL PORTALS IN UZBEKISTAN - Khumoyun Sayfullaev; Sitora Nurmatova; Mukhlisa Berdieva (Scholars Digest Publishing, 2023)
This study is designed to highlight the significance of online travel portals for supporting the tourism industry and encouraging further exploration of long-term growth prospects in Uzbekistan, a country with a growing tourism industry. The findings suggest that while the use of online travel portals is still relatively low in Uzbekistan, there is potential for growth due to the increasing number of internet users and the growing importance of online bookings in the global travel market. However, there are also challenges that need to be addressed, such as poor infrastructure and digital content. The research highlights the need for collaboration between online travel portals, traditional travel agencies, and tourism organizations to overcome these challenges and unlock the potential of the travel industry in Uzbekistan. Key factors that could contribute to the success of online travel portals in Uzbekistan include the availability of localized and relevant content, secure payment systems, and increased destination marketing efforts. The discussion is based on a mixed-method research design that incorporates a comprehensive literature review.
Keywords: Tourism development, online travel portals, travel industry, innovation, digital, Internet, Uzbekistan, consumer behavior, tourist, ICT (Information and Communication Technologies).